Back pain and MRI changes in the thoraco‐lumbar spine of young elite Mogul skiers. (1st July 2016) - Thoreson, O.; Kovac, P.; Swärd, A.; Agnvall, C.; Todd, C.; Baranto, A.
Abstract : Athletes have a higher prevalence of LBP and spinal abnormalities on Magnetic Resonance Imaging (MRI) compared to non‐athletes. The objective of this study was to investigate the amount of spinal MRI abnormalities and the lifetime prevalence of low back pain (LBP) in 16 young elite Mogul skiers compared to 28 non‐athletes in the corresponding age in a cross‐sectional design. LBP was assessed by a questionnaire consisting of a part regarding previous or present back pain, the Oswestry disability index, and the EuroQol questionnaire. MRI examinations from Th5 to sacrum were conducted to evaluate spinal pathologies. The Mogul skiers had significantly more MRI abnormalities (like disc degeneration) in mean (7.25 vs 3.78, P  < 0.023) compared to the controls. No significant difference was seen regarding the lifetime LBP prevalence between the groups (50% vs 42%, P  = 0.555). No correlation could be found between disc degeneration and back pain in this study. Young elite Mogul skiers, compared to an age‐matched control group of non‐athletes, have an increased risk of developing spinal abnormalities potentially due to the different high loads that they are subjected to in their sport. Future relationship between the MRI abnormalities and LBP cannot be verified by this study design.